1992
DOI: 10.1302/0301-620x.74b4.1624508
|View full text |Cite
|
Sign up to set email alerts
|

Plasma viscosity and C-reactive protein after total hip and knee arthroplasty

Abstract: We studied the changes in plasma viscosity and C-reactive protein to establish normal values after total hip or knee arthroplasty. The C-reactive protein level increased significantly on the first postoperative day and then decreased from a peak on the second day, attaining nearly normal levels at six to eight weeks after operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
0
3

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 0 publications
2
30
0
3
Order By: Relevance
“…Previous studies (Ellitsgaad et al 1991, Choudhry et al 1992, Kragsbjerg et al 1995 have reported that CRP levels depend on the region of trauma, with the maximum levels on the second postoperative day. Reliable data exist for hip fractures (Okafor and Maclellan 1998) and arthroplasty of the hip (Niskanen et al 1996, White et al 1998, reaching values of about 10-16 mg/dL for standard procedures, using a posterolateral or anterolateral approach.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies (Ellitsgaad et al 1991, Choudhry et al 1992, Kragsbjerg et al 1995 have reported that CRP levels depend on the region of trauma, with the maximum levels on the second postoperative day. Reliable data exist for hip fractures (Okafor and Maclellan 1998) and arthroplasty of the hip (Niskanen et al 1996, White et al 1998, reaching values of about 10-16 mg/dL for standard procedures, using a posterolateral or anterolateral approach.…”
Section: Discussionmentioning
confidence: 90%
“…and some studies involved TKA and THA, which reportedly differ in postoperative levels of CRP and ESR [2,5,8,10,14,20,22,25,30]. Despite the well-known wide variations in postoperative levels of CRP and ESR, some previous studies report temporal patterns based on the mean values but without detailed normative data [2,5,8,10,20,22,25] and the proportion of cases not following the typical temporal pattern was not reported in these series. Also, these studies did not explore the association between preoperative and postoperative levels of CRP and ESR.…”
Section: Introductionmentioning
confidence: 78%
“…Finally, the dominance of female patients in the current series should be considered. Erythrocyte sedimentation rate levels vary with gender [3,35], whereas CRP levels do not have a similar variation [5,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CRP is a marker of general tissue damage in addition to inflammation, which is also used in cardiology (Ledue and Rifai 2003). It is superior to the conventional parameters (leukocyte counts, erythrocyte sedimentation rate) in highlighting surgical complications with bacterial infection (Ellitsgaad et al 1991, Choudhry et al 1992). However, CRP was not found to be predictive of organ failure and sepsis in a small number of patients (Giannoudis et al 1998).…”
mentioning
confidence: 99%